Fermi surface of SrFe2P2 determined by the de Haas-van Alphen effect. - Analytis, J; Andrew, C; Coldea, A; McCollam, A; Chu, J; McDonald, R; Fisher, I; Carrington, A (2009)
We report measurements of the Fermi surface (FS) of the ternary iron-phosphide SrFe2P2 using the de Haas-van Alphen effect. The calculated FS of this compound is very similar to SrFe2As2, the parent compound of the high temperature superconductors. Our data show that the Fermi surface is composed of two electron and two hole sheets in agreement with band-structure calculations. Several of the sheets show strong c-axis warping emphasizing the importance of three dimensionality in the nonmagnetic state of the ternary pnictides. We find that the electron and hole pockets have a different topology, implying that this material does not satisfy a (pi, pi) nesting condition.